Överlevnad av Streptococcus equi subspecies equi på olika material i hästens omgivning - Andreasson, Mikaela (2018)
Strangles, caused by the bacteria Streptococcus equi subspecies equi (S. equi) is the most commonly diagnosed infectious disease in horses worldwide. Infection by S. equi in the upper respiratory tract results in fever, nasal discharge and enlarged lymph nodes that can contain abscesses. Strangles is highly contagious and can also in some cases cause serious complications and even fatalities. Spread of S. equi most commonly occurs via direct contact between horses, but also spreads indirectly via for example stable interior and equipment. While strangles as a clinical disease has been well described, whether, and if so, for how long the bacteria can survive on inanimate objects in the stable environment is poorly understood.